Laser surface melting to enhance surface properties in hot press forming die - Norhafzan, Bariman (2020)
Hot press forming (HPF) used to produced ultra-high strength component of automobile structure up to 1500 MPa. During HPF processes die works at temperatures between 600 and 850oC to form boron steel blank. During hot working processes the high temperatures and cyclic loading caused the HPF dies surface to lose strength and hardness and lead to failure and reduce quality product produced from HPF process. The main objective of this research is to produce high strength component via hot press forming with laser modified die inserts. The Nd:YAG laser system was used to process AISI H13 tool steel as die insert to formed 22MnB5 blank. The melted die surface was analysed for surface morphology, roughness, hardness, metallographic study, phase analysis, and chemical composition. The resultant outcomes of this study revealed the effect of laser processing parameters on the properties of the melted layer. The minimum surface roughness was 1.886 µm and maximum melted depth was 0.33 mm respectively when process at 70% overlapping rate due to slow solidification rate. Additionally, the surface hardness value of melted layer increased three time from its substrate up to 793.7 HV0.1, due to the grain structure of melted layer refined with an average grain size of 1.02 µm. Meanwhile, the peak intensity showed that high crystallite increased surface hardness of the melted layer. The HPF process to form 22MnB5 steel blank was conducted using 60-tonne hydraulic press machine with various die insert for 40 cycle per die insert. Rapid heat transfer across melted die surface during HPF processed produced high surface hardness of 22MnB5 blank up to 508.1 HV0.1 when formed using melted die insert. Fast heat transfer contributed to increased cooling rate and produce high strength component. The study was also aimed to determine the thermal properties of the die insert surface subjected to melting during the HPF process. Thermal distribution analysis of die insert surface indicates heat transfer from high temperature blank surface to the melted die insert during quenching process was up to 40.4oC. While the temperature for the as-received die recorded 60.9oC. Its shows that the cooling rate of laser melted die surface was higher than the cooling rate of as-received die insert. This study proved the significance of laser melted surface in enhancing the thermal properties of die surface and improving the quality of 22MnB5 after HPF process.